Characterization and cellular internalization of spherical cellulose nanocrystals (CNC) into normal and cancerous fibroblasts - Shazali, Nur Aima Hafiza; Zaidi, Noorzaileen Eileena; Ariffin, Hidayah; Abdullah, Luqman Chuah; Ghaemi, Ferial; Abdullah, Jafri Malin; Takashima, Ichiro; Nik Abd Rahman, Nik Mohd Afizan (MDPI, 2019)
The aim was to isolate cellulose nanocrystals (CNC) from commercialized oil palm empty fruit bunch cellulose nanofibre (CNF) through sulphuric acid hydrolysis and explore its safeness as a potential nanocarrier. Successful extraction of CNC was confirmed through a field emission scanning electron microscope (FESEM) and attenuated total reflection Fourier transmission infrared (ATR-FTIR) spectrometry analysis. For subsequent cellular uptake study, the spherical CNC was covalently tagged with fluorescein isothiocyanate (FITC), resulting in negative charged FITC-CNC nanospheres with a dispersity (Ð) of 0.371. MTT assay revealed low degree cytotoxicity for both CNC and FITC-CNC against C6 rat glioma and NIH3T3 normal fibroblasts up to 50 µg/mL. FITC conjugation had no contribution to the particle’s toxicity. Through confocal laser scanning microscope (CLSM), synthesized FITC-CNC manifested negligible cellular accumulation, indicating a poor non-selective adsorptive endocytosis into studied cells. Overall, an untargeted CNC-based nanosphere with less cytotoxicity that posed poor selectivity against normal and cancerous cells was successfully synthesized. It can be considered safe and suitable to be developed into targeted nanocarrier.